Level of professional culture University students in Jordan - Mohammad Omar AL-Momani; Purnawan Purnawan (Journal of Vocational Education Studies, 2022)
The study aimed to identify the level of professional culture of undergraduate students In Jordan from the point of view of the students themselves and its relationship to the gender variable, where the descriptive approach was used in addition to the use of the questionnaire as a study tool in the classroom. school the first of the academic year (2021-2022AD)The study sample consisted of (300) male and female students representing all levels and stages of university study. The study, after conducting the appropriate statistical treatments, concluded that the level of professional culture among students It reached (3.45) with a standard deviation of (0.54) and a mean total score, in addition to the absence of statistically significant differences in the level of professional culture for students, which are attributed to the gender variable.